2008
DOI: 10.1097/aln.0b013e318164ca9b
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Perioperative Adverse Respiratory Events in Children Who Are Obese

Abstract: These results suggest that children presenting for elective surgical procedures who are obese have a greater prevalence of preexisting comorbid medical conditions and an increased incidence of perioperative adverse respiratory events compared with normal-weight children. Identification and awareness of risk factors for perioperative complications will be important in optimizing the anesthetic management of these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 26 publications
(29 reference statements)
6
98
0
11
Order By: Relevance
“…Studies have shown that up to 70% of the pediatric patients have a history of URI within six weeks prior to surgery. [2][3][4][5] There have been reports of increased perioperative morbidity in children presenting to surgery with an actual or recent (\ six weeks) URI. 2,4 An increased number of episodes of laryngospasm, desaturation, increased oral secretion, and coughing has been observed at induction, emergence, and throughout the postoperative phase period.…”
Section: Résumémentioning
confidence: 99%
“…Studies have shown that up to 70% of the pediatric patients have a history of URI within six weeks prior to surgery. [2][3][4][5] There have been reports of increased perioperative morbidity in children presenting to surgery with an actual or recent (\ six weeks) URI. 2,4 An increased number of episodes of laryngospasm, desaturation, increased oral secretion, and coughing has been observed at induction, emergence, and throughout the postoperative phase period.…”
Section: Résumémentioning
confidence: 99%
“…5,6 Obese children and adolescents have an increased risk of type 2 diabetes mellitus, asthma, and nonalcoholic fatty liver disease; are more likely to have cardiovascular risk factors; and have greater anesthesia risk. [5][6][7] They may also experience more mental health and psychological issues such as depression 8 and low self-esteem 8-10 compared with nonobese children.…”
Section: Burden Of Diseasementioning
confidence: 99%
“…Knowledge of the clinical implications of obesity in children is limited, although obesity is associated with an increased risk of serious airway and respira- tory complications during and after anaesthesia [3]. Obese children are more likely to develop co-morbidities such as diabetes, fatty liver infiltration [20], obstructive sleep apnoea, hypertension and asthma [3].…”
Section: Discussionmentioning
confidence: 99%
“…Opioid-induced respiratory depression and paracetamol-induced hepatic injury are examples of potential harm due to accidental overdose. Obese children may also have related co-morbidities such as obstructive sleep apnoea or fatty infiltration of the liver [3]. Dose adjustment according to dosing scalars such as ideal body weight (IBW), lean body mass (LBM) and TBW depends upon the specific drug [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%